The effect of tax awareness, service quality, and tax sanctions on tax payment compliance at one stop administrator service - Ria Sandra Alimbudiono; Christine Gianina Sulistio (New Applied Studies in Management, Economics & Accounting)
This research aims to evaluate compliance with motor vehicle tax payments at the One-Stop Single Administration System (Samsat) in East Surabaya, using three variables: taxpayer awareness, service quality, and tax sanctions. A quantitative approach was employed, involving 136 participants who were taxpayers registered with the East Surabaya Samsat and remained active until 2023, owning private two-wheeled motor vehicles. Data were collected through a questionnaire distributed via Google Forms. Before analysis, validity and reliability tests were conducted, and the data were analyzed using SPSS software. The results indicate that the three variables significantly influence compliance with motor vehicle tax payments at the East Surabaya Samsat, with taxpayer awareness being the most impactful factor. Future research is encouraged to use more recent data for improved accuracy and reliability and to explore additional variables that have not yet been examined.